Girls with highly educated parents have less somatic complaints (Sociologisk Forskning, 2017)
In Sweden, as in Western countries generally, somatic complaints are common in adolescents. These complaints are clearly connected with gender while the evidence of socioeconomic inequalities is less conclusive. The aim of this study is to analyse the combined relevance of gender and parental education for adolescents’ somatic complaints, using national data with direct information from adolescents and their parents (n=7,393). Among girls, but not among boys, a graded association was found demonstrating less somatic complaints with higher parental education. Stress and coping are discussed as potentially important mechanisms.
Keywords: adolescence; health complaints; inequalities